Factors Affecting Social Science Teachers’ Burnout in Selected State Universities in the Philippines - Pimentel, Marivic Mendoza (Asia Pacific Higher Education Research Journal (APHERJ), 2017)
This study aimed to find out the factors affecting Social Science teachers’ burnout in selected State Universities in the Philippines in terms of job assignment, organizational, human relations, physical environment and out-of-school related factors. This study was also conducted to know the three distinct dimensions of burnout as experienced by the Social Science teachers with regard to reduced self-efficacy, exhaustion and pessimism and negativity towards others and work. There were 54 full-time Social Science teachers in selected State Universities in the Philippines who participated in this descriptive research. The Teacher Burnout Instrument (TBI) and the survey questionnaire determined the factors affecting Social Science teachers’ burnout. Result revealed that the level of Social Science teacher burnout on the three components: Component 1-Reduced Self-Efficacy (M=45.25), Component 2-Exhaustion (M=26.39) and Component 3-Pessimism and Negativity Towards Others and Work (M=17.12) is within the average. Findings also show that while average burnout level appears to be tolerable, it may indicate a tendency for burnout to escalate to a more serious level and therefore need to addressed by the institutions (SUCs). And based on the identified factors affecting Social Science teachers, the Teacher Burnout Intervention Program (TBIP) is designed individual directed and organizational directed.